Renewable cellulosic nanocomposites for food packaging to avoid fossil fuel plastic pollution: a review - Umair Qasim; Ahmed I. Osman; Ala’a H. Al-Muhtaseb; Charlie Farrell; Mohammed Al-Abri; Muzaffar Ali; Dai-Viet N. Vo; Farrukh Jamil; David W. Rooney (Environmental Chemistry Letters, 2021)
The extensive use of petroleum-based synthetic and non-biodegradable materials for packaging applications has caused severe environmental damage. The rising demand for sustainable packaging materials has encouraged scientists to explore abundant unconventional materials. For instance, cellulose, extracted from lignocellulosic biomass, has gained attention owing to its ecological and biodegradable nature. This article reviews the extraction of cellulose nanoparticles from conventional and non-conventional lignocellulosic biomass, and the preparation of cellulosic nanocomposites for food packaging. Cellulosic nanocomposites exhibit exceptional mechanical, biodegradation, optical and barrier properties, which are attributed to the nanoscale structure and the high specific surface area, of 533 m 2 g −1 , of cellulose. The mechanical properties of composites improve with the content of cellulose nanoparticles, yet an excessive amount induces agglomeration and, in turn, poor mechanical properties. Addition of cellulose nanoparticles increases tensile properties by about 42%. Barrier properties of the composites are reinforced by cellulose nanoparticles; for instance, the water vapor permeability decreased by 28% in the presence of 5 wt% cellulose nanoparticles. Moreover, 1 wt% addition of filler decreased the oxygen transmission rate by 21%. We also discuss the eco-design process, designing principles and challenges.

Advanced materials and technologies for supercapacitors used in energy conversion and storage: a review - M. I. A. Abdel Maksoud; Ramy Amer Fahim; Ahmed Esmail Shalan; M. Abd Elkodous; S. O. Olojede; Ahmed I. Osman; Charlie Farrell; Ala’a H. Al-Muhtaseb; A. S. Awed; A. H. Ashour; David W. Rooney (Environmental Chemistry Letters, 2021)
Supercapacitors are increasingly used for energy conversion and storage systems in sustainable nanotechnologies. Graphite is a conventional electrode utilized in Li-ion-based batteries, yet its specific capacitance of 372 mA h g −1 is not adequate for supercapacitor applications. Interest in supercapacitors is due to their high-energy capacity, storage for a shorter period and longer lifetime. This review compares the following materials used to fabricate supercapacitors: spinel ferrites, e.g., MFe 2 O 4 , MMoO 4 and MCo 2 O 4 where M denotes a transition metal ion; perovskite oxides; transition metals sulfides; carbon materials; and conducting polymers. The application window of perovskite can be controlled by cations in sublattice sites. Cations increase the specific capacitance because cations possess large orbital valence electrons which grow the oxygen vacancies. Electrodes made of transition metal sulfides, e.g., ZnCo 2 S 4 , display a high specific capacitance of 1269 F g −1 , which is four times higher than those of transition metals oxides, e.g., Zn–Co ferrite, of 296 F g −1 . This is explained by the low charge-transfer resistance and the high ion diffusion rate of transition metals sulfides. Composites made of magnetic oxides or transition metal sulfides with conducting polymers or carbon materials have the highest capacitance activity and cyclic stability. This is attributed to oxygen and sulfur active sites which foster electrolyte penetration during cycling, and, in turn, create new active sites.

Production and characterisation of activated carbon and carbon nanotubes from potato peel waste and their application in heavy metal removal. - Ahmed I. Osman; Jacob Blewitt; Jehad K. Abu-Dahrieh; Charlie Farrell; Ala’a H. Al-Muhtaseb; John Harrison; David W. Rooney (Environmental Science and Pollution Research, 2019)
Herein, activated carbon (AC) and carbon nanotubes (CNTs) were synthesised from potato peel waste (PPW). Different ACs were synthesised via two activation steps: firstly, with phosphoric acid (designated PP) and then using potassium hydroxide (designated PK). The AC produced after the two activation steps showed a surface area as high as 833 m 2 g −1 with a pore volume of 0.44 cm 3 g −1 , where the raw material of PPW showed a surface area < 4 m 2 g −1 . This can help aid and facilitate the concept of the circular economy by effectively up-cycling and valorising waste lignocellulosic biomass such as potato peel waste to high surface area AC and subsequently, multi-walled carbon nanotubes (MWCNTs). Consequently, MWCNTs were prepared from the produced AC by mixing it with the nitrogen-based material melamine and iron precursor, iron (III) oxalate hexahydrate. This produced hydrophilic multi-wall carbon nanotubes (MWCNTs) with a water contact angle of θ = 14.97 °. Both AC and CNT materials were used in heavy metal removal (HMR) where the maximum lead absorption was observed for sample PK with a 84% removal capacity after the first hour of testing. This result signifies that the synthesis of these up-cycled materials can have applications in areas such as wastewater treatment or other conventional AC/CNT end uses with a rapid cycle time in a two-fold approach to improve the eco-friendly synthesis of such value-added products and the circular economy from a significant waste stream, i.e., PPW.

A Continental-Scale Validation of Ecosystem Service Models - Simon Willcock; Danny A. P. Hooftman; Stefano Balbi; Ryan Blanchard; Terence P. Dawson; Patrick J. O’Farrell; Thomas Hickler; Malcolm D. Hudson; Mats Lindeskog; Javier Martinez-Lopez; Mark Mulligan; Belinda Reyers; et al. (Ecosystems, 2019)